Characterization of Fluorescent Dyes Frequently Used for Bioimaging: Photophysics and Photocatalytical Reactions with Proteins - Archipowa, Nataliya; Wittmann, Lukas; Köckenberger, Johannes; Ertl, Fabian J.; Gleixner, Jakob; Keller, Max; Heinrich, Markus; Kutta, Roger Jan (Journal of Physical Chemistry B, 2023)
Derivatives of the rhodamine-based dye 5-TAMRA (5-carboxy-tetramethylrhodamine) and the indocarbocyanine-type Cy3B (cyclized derivative of the cyanine dye Cy3), both representing important fluorophores frequently used for the labeling of biomolecules (proteins, nucleic acids) and bioactive compounds, such as receptor ligands, were photophysically investigated in aqueous solution, i.e., in neat phosphate-buffered saline (PBS) and in PBS supplemented with 1 wt % bovine serum albumin (BSA). The dyes exhibit comparable absorption (λabs,max: 550-569 nm) and emission wavelengths (λem,max: 580-582 nm), and similar S1 lifetimes (2.27-2.75 ns), and their excited state deactivation proceeds mainly via the lowest excited singlet state (triplet quantum yield ca. 1%). However, the probes show marked differences with respect to their fluorescence quantum yield and photostability. While 5-TAMRA shows a lower quantum yield (37-39%) than the Cy3B derivative (ca. 57%), its photostability is considerably higher compared to Cy3B. Generally, the impact of the protein on the photophysics is low. However, on prolonged illumination, both fluorescent dyes undergo a photocatalytic reaction with tryptophan residues of BSA mediated by sensitized singlet oxygen resulting in a tryptophan photoproduct with an absorption maximum around 330 nm. The overall results of this work will assist in choosing the right dye for the labeling of bioactive compounds, and the study demonstrates that experiments performed with 5-TAMRA or Cy3B-labeled compounds in a biological environment may be influenced by photochemical modification of experimentally relevant proteins at aromatic amino acid residues.
CRIS-Team Scopus Importer:2023-11-24